Notes about Comparing Long-Term Care Expenditures across Countries. Comment on "Financing Long-Term Care: Lessons from Japan" - Johannes Geyer (International Journal of Health Policy and Management, 2020)
The comparison of long-term care (LTC) expenditures is a difficult task. National LTC systems differ widely in terms of eligibility criteria, level of benefits, institutional variety and regional heterogeneity. In this commentary I will first give some general remarks on cross country comparisons. Then I discuss the role of the informal sector which is the most important pillar of all LTC systems. I conclude with some background on current developments in Germany. Different from Japan Germany is extending its LTC insurance instead of containing costs.
Keywords: 330; Long-term care; Social insurance; International comparison; Public expenditures